Clinical Manifestation, Histopathology, and Imaging of Traumatic Injuries Caused by Brazilian Porcupine (Sphiggurus villosus) Quills. (17th November 2016) - Jorge, Lívia M. Araújo; Bernardes Filho, Fred; Lamy, Fabrício; Balassiano, Laila Klotz A.; Towersey, Loan; Hay, Roderick; Frade, Marco Andrey C.
Abstract : Injuries to humans caused by porcupines are rare. However, they may occur due to the proximity of urban areas and the animal's habitat in areas such as the Floresta da Tijuca in Rio de Janeiro. Outdoor sports and leisure activities in areas close to forests or in the rain forest are also relevant for incidents of this kind and a better knowledge of the local forest fauna would prevent such undesirable accidents. Porcupine quills have microscopic barbs at their tips which facilitate skin penetration, but hampering their removal. Once the spines are lodged in tissue, the microscopic backward-facing deployable barbs at the tips cause trauma if anyone tries to remove them. Local haemorrhage and an inflammatory response to the contaminated foreign body occur. Depending on the time lapse in removing the spines either septic or sterile foreign body reactions may occur. There is also the risk of migration of the spines, where fatal cases have been reported in human and veterinary medicine. Herein we report two unusual cases of accidents involving humans and the South American porcupine. The Sphiggurus villosus spines removed from scalp skin were also documented through Scanning Electron Microscopy.